2022
DOI: 10.1186/s12909-022-03312-y
|View full text |Cite
|
Sign up to set email alerts
|

The development of empathy in the healthcare setting: a qualitative approach

Abstract: Background Healthcare professionals’ empathetic behaviors have been known to lead to higher satisfaction levels and produce better health outcomes for patients. However, empathy could decrease over time especially during training and clinical practice. This study explored factors that contributed to the development of empathy in the healthcare setting. Findings could be used to improve the effectiveness and sustainability of empathy training. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Based on the results of pathway analysis, empathy had a positive correlation with work-related perception with the factor load of 0.26, which provided evidence to support H2. Work-related perception was considered a medium stability factor in the tentative theory of empathy development proposed by Yu et al A medium stability factor often represents long-standing environmental and personal limitations and may be associated with the level of empathy (Yu et al, 2022). In line with this, a cross-sectional study conducted in India found that dental interns and graduate students showed a positive correlation between empathy score and work satisfaction (Rajput et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of pathway analysis, empathy had a positive correlation with work-related perception with the factor load of 0.26, which provided evidence to support H2. Work-related perception was considered a medium stability factor in the tentative theory of empathy development proposed by Yu et al A medium stability factor often represents long-standing environmental and personal limitations and may be associated with the level of empathy (Yu et al, 2022). In line with this, a cross-sectional study conducted in India found that dental interns and graduate students showed a positive correlation between empathy score and work satisfaction (Rajput et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that topics related to artificial intelligence and automation will emerge in these narratives. Surveys [ 59 ], interviews [ 60 ], and big data analytics [ 61 , 62 ] could also be used to explore the types of stereotypes linked to professionals of different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Work engagement is, aside of autonomy, also supported by job resources including supervisor support, fair and authentic management, transformational leadership, professional resources (Broetje et al, 2020) Other research also showed empathy to result in higher levels of patient satisfaction and in (small) improvements of psychological (pain and anxiety) patient outcomes (Howick et al, 2018). Thus empathy is considered a valuable resource of nurses, which has been described as a rather stable individual trait (inherent characteristics, physiological and mental states, professional identity), while it can also be affected by situational factors (work environment, life experience, situational stressors; Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%